Relationship between childhood trauma and obsessive-compulsive disorder - Mustafa, Ali Burhan; Shehzadi, Irum; Nargis, Fasiha; Mustafa, Urooj Burhan; Makhdoom, Bisma Jamil; Batool, Sadia; Ghaffar, Rafia (Journal of Pakistan Psychiatric Society, 2021)
OBJECTIVE: The high prevalence rate of obsessive-compulsive disorder in patients with the history of childhood traumas is commonly reported. The current study aimed to investigate the relationship between child sexual, emotional and physical abuse to the onset and course of OCD.PLACE AND DURATION OF THE STUDY: This study was conducted in Department of Psychiatry and Behavioral Sciences Sheikh Zayed Medical College/Hospital, Rahim Yar Khan, from July 2019 to January 2020.SUBJECT AND METHODOLGY: In this study cross-sectional research design and purposive sampling technique was used.  Data was retrieved from 100 patients diagnosed with obsessive compulsive disorder. Additionally childhood traumas were assessed by Childhood trauma questionnaire (CTQ) developed by David. P, Brenstine.RESULTS: Results shows that Obsessive Compulsive Disorder was partly significantly correlated with Childhood Trauma and well as subscale. The range of value from (.21** to .44**) and there was no significant difference among gander related to there childhood Truman and other subscale. The mean and SD value are very close for child trauma  (Male M = 24.23, SD = 9,71), (Female M = 24.11, SD = 9,82).Analysis suggests a significant relationship between child sexual, emotional and physical abuse in OCD.Furthermore it is suggests for the future study the victims of CSA have contact with mental health services earlier in life, it’s better for the generalization and validation for future study.